T-Mobile: strategic decisions to improve position in the market - Whatling, Shaun (Henry Stewart Talks, 2016)
The case study analyses the strategic decisions (including advertising and marketing) by a well-known brand to improve its position in the market and put competitive pressure on other firms. This includes the results from trialling sponsorship of music and film events.